UKURAN PERUSAHAAN DAN TINGKAT LEVERAGE SEBAGAI PENDORONG PENERAPAN HEDGING UNTUK MENEKAN RISIKO IDIOSINKRATIK - Cesilia Novita Simarmata; Suwandi Ng; Fransiskus E. Daromes (AJAR, 2019)
This research aims to investigate the role of firm size and leverage to be determinants of hedging application in order to suppress idiosyncratic risk. This research measured firm size using natural logarithm of total assets, debt to equity ratio for leverage, dummy variable for hedging activity, and Three Factor Model by Fama and French for idiosyncratic risk. The main theory used in these research are signaling theory and agency theory. The population used is non-financial companies listed on the Indonesian Stock Exchange for period of 2013-2017. The number of samples are 94 firms each year, selected by purposive sampling method. This research used documentary data, such as the annual report and financial statements. This research also used path analysis to analyze the data and sobel test to analyze the mediation role of hedging. The results of this research show that firm size and leverage have a positive and significant effect to hedging. Firm size has a positive but not significant effect to idiosyncratic risk, whilst leverage has a positive and significant effect to the latter. Firm size has a significant effect to idiosyncratic risk through hedging activity as mediator. Surprisingly, leverage does not need hedging to mediate its effect to idiosyncratic risk. This research is expected to be a reference for management to improve firm performance so it could gain investor trusts through hedging application as financial strategy. Investor could also use the results of this research as considerations for investment decision making.